Technologies and Education: Their Social Perception in Santiago de Chile [Tecnologías y Educación: Su Percepción Social en Santiago de Chile] - Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2017)
The article shows the results of a study developed in three areas of the Metropolitan Region in Chile, in which 1228 people of different age, labor, educational level, and gender were surveyed. The validated instrument consists of four dimensions students, teaching, teaching quality, interpersonal relations and relationship with technology. The instrument was designed to know the perception of the population about the relationship between education and technology. The analysis showed a society that is permissive with respect of the introduction of technologies in the educational processes, in agreement with previous studies. However, there is skepticism about the contribution of technology for improving interpersonal relations. Another interesting result is that there is a clear interest and position of the people about technology, either in favor or against it. Only 3% of the population surveyed has an indifferent position.